2018
DOI: 10.15171/jlms.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Low-Level Laser Therapy – A Complementary Treatment in the Management of Side Effects After Implant Surgery

Abstract: Previous studies have shown that LLLT can be effective to accelerate healing and pain relief through reduction of mediators and inflammatory cells and increased endorphin, respectively. 13 This modality is acceptable and cost-effective. 13,14 Many dentists use identical drugs for different treatments and there is no agreement to prescribe the drugs based on the patient's health status. 15,16 The aim of this study was to investigate the effect of LLLT using 830 nm wavelength and 120 mW power in the management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…There are more reports on red light than on green or blue light, and basic research has been carried out on its bioactivation effects 22) . Clinical studies in the dental field have reported that it promotes oral wound healing 23,24) and implant stability [25][26][27] . Blue light sources are used for the treatment of acne vulgaris, psoriasis, etc., and their results are often evaluated through mechanisms, such as bactericidal effects due to increased reactive oxygen species and induction of cell apoptosis 28) .…”
Section: Photobiomodulation Therapy (Pbmt)mentioning
confidence: 99%
“…There are more reports on red light than on green or blue light, and basic research has been carried out on its bioactivation effects 22) . Clinical studies in the dental field have reported that it promotes oral wound healing 23,24) and implant stability [25][26][27] . Blue light sources are used for the treatment of acne vulgaris, psoriasis, etc., and their results are often evaluated through mechanisms, such as bactericidal effects due to increased reactive oxygen species and induction of cell apoptosis 28) .…”
Section: Photobiomodulation Therapy (Pbmt)mentioning
confidence: 99%